2011
DOI: 10.1002/pbc.23082
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved parental evaluation of the quality of a palliative care program in Lebanon

Abstract: This study is the first conducted in Lebanon to evaluate the quality of pediatric palliative care (PPC). The parents' experiences in our country were similar to those described in other countries, religions, and cultures. Significant strengths and weaknesses in the management of the dying children, from the parents' perspective, were uncovered and recommendations for improving practice were made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…Manuscripts represented data from nine countries: Australia, 24,26,31,36 Brazil, 12 Canada, 2,23,37,38,43,66 Germany, 32,40 Lebanon, 18 Netherlands, 44 Sweden, 33,39 United Kingdom, 17 the United States, 1316,19,20,22,25,28,29,45 and one multi-country paper. 41 The primary study subject included pediatric ages, 42 the adolescent young adult (AYA) population ages 10–21, 22 14–21, 34 16–28, 19,28 and 15–25 years; 66 caregivers of patients receiving palliative care; 3,12,13,15,24,29,37,38,43,81 bereaved parents; 2,14,18,20,23,2527,3133,35,36,39,40,44,45 social workers; 16 principal investigators; 41 palliative team members; 17 and pediatric oncologists. 30 Five original research studies reported on a specific intervention other than the development of a palliative care service: use of family-centered ACP training, 34 parental decision rationale reported in timely summary for medical teams, 15 introduction of co-case management and shared decision-making education, 29 a 24-hour available palliative telephone service, 24 and advanced practice palliative staff training for transitions from critical care settings.…”
Section: Resultsmentioning
confidence: 99%
“…Manuscripts represented data from nine countries: Australia, 24,26,31,36 Brazil, 12 Canada, 2,23,37,38,43,66 Germany, 32,40 Lebanon, 18 Netherlands, 44 Sweden, 33,39 United Kingdom, 17 the United States, 1316,19,20,22,25,28,29,45 and one multi-country paper. 41 The primary study subject included pediatric ages, 42 the adolescent young adult (AYA) population ages 10–21, 22 14–21, 34 16–28, 19,28 and 15–25 years; 66 caregivers of patients receiving palliative care; 3,12,13,15,24,29,37,38,43,81 bereaved parents; 2,14,18,20,23,2527,3133,35,36,39,40,44,45 social workers; 16 principal investigators; 41 palliative team members; 17 and pediatric oncologists. 30 Five original research studies reported on a specific intervention other than the development of a palliative care service: use of family-centered ACP training, 34 parental decision rationale reported in timely summary for medical teams, 15 introduction of co-case management and shared decision-making education, 29 a 24-hour available palliative telephone service, 24 and advanced practice palliative staff training for transitions from critical care settings.…”
Section: Resultsmentioning
confidence: 99%
“…We described additional instrumental difficulties parents face when caring for a child with LTI, such as safe, secure, affordable childcare arrangements for the healthy siblings that can allow families to connect with both their ill and healthy children and flexible employment options. Parents’ description of needs here provides a glimpse into the seemingly small, but cumulative costs they encounter, direct medical costs and also indirect costs related to caring for the ill child, that contribute to loss of family income as reported in the literature (Hechler et al, 2008; Saad, 2008; Tomlinson et al, 2011). Contrary to the tenets of family centered care (Harrison, 2010; Shelton & Stepanek, 1994), our study demonstrates broader cost-related issues may be addressed late or at a point of financial emergency.…”
Section: Discussionmentioning
confidence: 99%
“…A simplified approach to consider anti-emetic medications for children with ALL is presented in TABLE 2, and this should be specifically adapted to each center with creation of written local guidelines that use inexpensive, locally available agents whenever possible. In addition to managing treatmentassociated symptoms, symptom anticipation and control are crucial for children with cancer at the end of life [105,106]. In all cases, in addition to feasibility, cost and training needs, local health beliefs and cultural acceptability of proposed interventions warrant consideration.…”
Section: Pain and Symptom Managementmentioning
confidence: 99%
“…Clear and timely communication has vital implications on perceived care quality and parental coping, including in preparation for patients' end-of-life [86,106,107]. Decision-making support should be offered at critical junctures, such as at the time of disease progression, relapse and transition from a curative goal of care to treatment with palliative-only intent.…”
Section: Communication and Decision-making Supportmentioning
confidence: 99%